2004
DOI: 10.1081/scc-120034170
|View full text |Cite
|
Sign up to set email alerts
|

Acylative Dimerization of Tetrahydrofuran Catalyzed by Rare‐Earth Triflates

Abstract: Ytterbium, scandium, and lanthanum triflates catalyze the cleavage reactions of cyclic ethers to give various products. Most notable was the acylative cleavage of tetrahydrofuran with acetic anhydride catalyzed by Yb(triflate) 3 to give the dimeric compound CH 3 CO 2 (CH 2 ) 4 O(CH 2 ) 4 OCOCH 3 in 69% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…of its ease of setup, mild conditions, rapid reaction, selectivity, increased yields [14], high purity of products and low cost, compared with their homogeneous counterparts [15]. It has been used as an efficient heterogeneous acid catalyst for ketal formation or acetalization [16], deprotection of acetals [17], tetrahydropyranylation of hydroxy compounds [18], esterification of cyclic olefins with aliphatic acids under solvent-free conditions [19], the Beckmann rearrangement of ketoxime [20] in dried CH 3 CN, and transesterification of β-ketoesters in ionic liquid [21].…”
Section: Introductionmentioning
confidence: 98%
“…of its ease of setup, mild conditions, rapid reaction, selectivity, increased yields [14], high purity of products and low cost, compared with their homogeneous counterparts [15]. It has been used as an efficient heterogeneous acid catalyst for ketal formation or acetalization [16], deprotection of acetals [17], tetrahydropyranylation of hydroxy compounds [18], esterification of cyclic olefins with aliphatic acids under solvent-free conditions [19], the Beckmann rearrangement of ketoxime [20] in dried CH 3 CN, and transesterification of β-ketoesters in ionic liquid [21].…”
Section: Introductionmentioning
confidence: 98%
“…It is commercially available and is a very cheap chemical. Recently, it was shown that sulfamic acid has the potential for use as a substitute for conventional acidic catalytic materials owing to its ease of set‐up, mild conditions, rapid reaction, selectivity, good yield, high purity of products and low cost, compared to its homogeneous counterparts . Silica‐supported sulfamic acid is a heterogeneous counterpart of sulfamic acid and has many advantages over sulfamic acid, such as recyclability, easy separation of catalyst and products, long catalytic life and thermal stability.…”
Section: Introductionmentioning
confidence: 99%